Mass and volume contributions to twentieth-century global sea level rise - Miller, Laury; Douglas, Bruce C. (Nature, 2004)
The rate of twentieth-century global sea level rise and its causes are the subjects of intense controversy 1 , 2 , 3 , 4 , 5 , 6 , 7 . Most direct estimates from tide gauges give 1.5–2.0 mm yr -1 , whereas indirect estimates based on the two processes responsible for global sea level rise, namely mass and volume change, fall far below this range. Estimates of the volume increase due to ocean warming give a rate of about 0.5 mm yr -1 (ref. 8 ) and the rate due to mass increase, primarily from the melting of continental ice, is thought to be even smaller. Therefore, either the tide gauge estimates are too high, as has been suggested recently 6 , or one (or both) of the mass and volume estimates is too low. Here we present an analysis of sea level measurements at tide gauges combined with observations of temperature and salinity in the Pacific and Atlantic oceans close to the gauges. We find that gauge-determined rates of sea level rise, which encompass both mass and volume changes, are two to three times higher than the rates due to volume change derived from temperature and salinity data. Our analysis supports earlier studies that put the twentieth-century rate in the 1.5–2.0 mm yr -1 range, but more importantly it suggests that mass increase plays a larger role than ocean warming in twentieth-century global sea level rise.